Pattern Recognition in Computing Education: A Systematic Review - Silva Junior, Braz Araujo da; Silva, Júlia Veiga da; Cavalheiro, Simone André da Costa; Foss, Luciana (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2022)
This paper presents a systematic literature review to investigate how pattern recognition has been approached in computing education. Pattern Recognition has long been an important concept among various areas, from cognitive psychology and neuroscience to machine learning and computer vision. Recently, it gained the attention of education, being associated with computational thinking. An old concept being revisited in a new context raises important questions on how it is being approached, how it is being assessed and if it is making use of previous contributions from the other fields that have been studying the concept. This work systematically reviews the literature to answer these questions on pattern recognition. It is found that, as other concepts related with computational thinking, it is rarely treated alone and when among others, few studies have pattern recognition as the main theme. The results also show that no standardized assessment method is used and contributions from other fields are barely mentioned.